Development of an adaptable garment design that can address the clothing-related physiological needs of children disaster survivors in evacuation centers in the Philippines - Tan, Alyssa M.; Maristela, Candy Mae M. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
The Philippines is a country prone to different man-induced and natural disasters. These disasters may vary in intensity but the common results are major and minor devastations in different communities leading to evacuation, or worse, displacement. In 2015, a study on functionality clothing for natural disaster survivors was conducted by Ahsan and Tullio-Pow. The authors were able to develop and create a multi-functional prototype called Survival Plus based on the perspective and clothing requirements of earthquake disaster survivors. This study developed an adaptable garment design for three-to five-year-old children disaster survivors situated in evacuation centers. The main factors studied to identify, and develop an adaptable garment design and features were the situation of selected evacuation center, physical activities of children and their physiological needs gathered from the perspective of parent/guardian evacuees. The study is descriptive in nature where the data attributed to the development of adaptable garment design are mostly qualitative. The data set for each factors were gathered through observation of an active evacuation center in Cebu City, personal interview, and survey with Cebu City Risk Reduction Management Office (CCDRRMO) Administration Aide, Social Worker, and 30 parent/guardian evacuees with three-to five-year-old children. Based on the analysis of data on issues and concerns related to children's physical activities and physiological needs affected by the situation in the evacuation center, it was found out that a set of adaptable garments is most compatible with children disaster survivors. A set with multifunctional garments with features on improved visibility to adapt to poorly lit evacuation centers, and made of comfortable materials with breathable and cooling properties to adjust to usually humid temperature in evacuation centers was designed to address the clothing-related needs of children disaster survivors.
submitted June 2018
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Children's clothing -- Philippines